Age specific clinicopathological profile of ovarian mass - Karki, Laxmi R.C.; Bogati, Nishchal (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Ovarian cancer is seventh leading cause of cancer death among women. Ovarian mass has age specific occurrence and may may help in screening and management plans. This study was conducted to determine the age-wise clinical profile of the ovarian mass. Methods: This review done to analyse the histologically diagnosed ovarian masses in cases operated during three years at Patan Hospital, Patan Academy of Health Sciences, Nepal. Clinical profile of the patients and age-wise distribution of histological types of ovarian mass were analyzed descriptively using Microsoft Excel. Results: Peak incidence of ovarian tumor was in age group of 20-29 years with 93 (36%) cases out of 258 ovarian masses. All eight malignant tumors were in age group of ≥40 years. Neoplastic masses were 188 (72.9%), 95 (50.5%) germ cell tumor. In 70 (27.1%) non-neoplastic lesion, corpus luteal cyst were 24 (34.3%). Conclusions: Peak incidence of ovarian tumor was seen in age group of 20-29 years. Germ cell tumors accounted for half of the neoplastic lesions. All malignant ovarian tumors were in found in age group ≥40 years.